1999
DOI: 10.1002/(sici)1521-3862(199903)5:2<65::aid-cvde65>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Highly Volatile, Low Melting, Fluorine-Free Precursors for Metal-Organic Chemical Vapor Deposition of Lanthanide Oxide-Containing Thin Films

Abstract: cm 3 in comparison to 1.8 g/cm 3 obtained for SiBCN 3 synthesized by polymer pyrolysis. High hardness values up to 22 GPa are found, which might be further increased by reducing the residual hydrogen content by applying higher bias potentials or by reduced precursor flow.Metal-organic chemical vapor deposition (MOCVD) is already an indispensable thin film growth technique for advancing microelectronics technologies, and it is predicted to play an even larger role in the future. [1] The inherent advantages of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 11 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…A key requirement for viable MOCVD processes is the availability of high-purity, thermally stable, volatile, and preferably low-melting metalorganic precursors having appropriate reactivity patterns to achieve efficient transport of the respective metal sources for clean film growth. Building on results from previous oxide growth studies, [26][27][28][29] known and new families of multidentate ligands that saturate the metal coordination sphere have been implemented in precursor synthesis and MOCVD growth of TCO films. Figure 4 illustrates several families of precursors that have been studied at Northwestern.…”
Section: Thin Films Of Transparent Conducting Oxidesmentioning
confidence: 99%
“…A key requirement for viable MOCVD processes is the availability of high-purity, thermally stable, volatile, and preferably low-melting metalorganic precursors having appropriate reactivity patterns to achieve efficient transport of the respective metal sources for clean film growth. Building on results from previous oxide growth studies, [26][27][28][29] known and new families of multidentate ligands that saturate the metal coordination sphere have been implemented in precursor synthesis and MOCVD growth of TCO films. Figure 4 illustrates several families of precursors that have been studied at Northwestern.…”
Section: Thin Films Of Transparent Conducting Oxidesmentioning
confidence: 99%
“…Tris­[ N , N -bis­(trimethylsilyl)­amido]­lanthanide complexes (Ln­[N­(SiMe 3 ) 2 ] 3 , abbreviated here as Ln NTMS ) are encountered frequently in the lanthanide catalysis literature, both as precursors to more complex lanthanide organometallics and as homogeneous catalysts, particularly for hydro-functionalization/reduction of alkenes and alkynes. These complexes are commercially available for many lanthanides, or can be readily synthesized and purified, rendering them highly accessible and of great interest to the synthetic methods community. A report from the Marks laboratory showed that it is possible to carry out the catalytic synthesis of amides with Ln NTMS , but the La NTMS -catalyzed reduction of amides had not yet been investigated. Given this, and the proven ability of La NTMS to catalyze carbonyl hydroboration, La NTMS -catalyzed amide hydroboration was an intriguing target.…”
Section: Introductionmentioning
confidence: 99%
“…Several lanthanide diketonate adducts with polyethers (Drake et al 1993a,b;Bradley et al 1994;Baxter et al 1995) and lanthanide ketoiminates (Belot et al 1999) have been developed with a view to using them as precursors for the *Author for correspondence (shivu@mrc.iisc.ernet.in) deposition of thin films of lanthanide-containing oxides. Some of these adducts exhibit improved properties over the β-diketonates, in terms of thermal stability and volatility, and are of potential interest for application as MOCVD precursors.…”
Section: Introductionmentioning
confidence: 99%